SOCIO-CULTURAL CONTRASTIVE STUDY IN THE EXPRESSION OF SWEAR WORDS BETWEEN ETHNIC INDONESIANS AND ETHNIC ARABS BASED ON SOCIOLINGUISTIC ANALYSIS - Muhammad Syaiful Bahri Hidayat; Jumriyah Jumriyah; Nur Cholis Agus Santoso; Damayanti Masduki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to contrastively examine the use of swear words in social interaction between Indonesian and Arab ethnicities based on sociolinguistic analysis. Swear words are part of everyday communication that can serve as emotional expressions, humour, solidarity, or even insults, depending on the social and cultural context in which they are used. This study reveals how cultural values, social norms, and linguistic factors influence the use and acceptance of swear words in both ethnic groups. This study uses a sociolinguistic approach to understand the social factors that influence swearing, contrastive analysis to compare the structure and meaning of swear words in Indonesian and Arabic, and ethnography of communication to examine the situation of using swear words in daily life. Data were collected through observation, interviews, and text analysis from social media, films, and oral interactions. The results show that there are differences in the patterns of swear word usage between the two ethnicities. In Arabic culture, swear words are mostly related to family honour, social status, and religion, so their use is more limited and can trigger serious conflicts. Meanwhile, in Indonesian culture, swear words have a wider variety and can function as expressions of anger, jokes, or even forms of familiarity, depending on the social relationship between the speaker and the listener. Moreover, the intensity and social acceptability of swearing varies by region and age group. This research provides new insights into how language as a reflection of culture can influence the way individuals express emotions and interact in society. The findings also have implications for the study of cross-cultural communication, language learning, as well as an understanding of the social and psychological impact of swear word use in everyday interactions.